Proteome Analysis of Dormancy-Released Seeds of Fraxinus mandshurica Rupr. in Response to Re-Dehydration under Different Conditions - Zhang, Peng (Int J Mol Sci, 2015)
Desiccation tolerance is the ability of orthodox seeds to achieve equilibrium with atmospheric relative humidity and to survive in this state. Understanding how orthodox seeds respond to dehydration is important for improving quality and long-term storage of seeds under low temperature and drought stress conditions. Long-term storage of seeds is an artificial situation, because in most natural situations a seed that has been shed may not remain in a desiccated state for very long, and if dormant it may undergo repeated cycles of hydration. Different types of seeds are differentially sensitive to desiccation and this directly affects long-term storage. For these reasons, many researchers are investigating loss of desiccation tolerance during orthodox seed development to understand how it is acquired. In this study, the orthodox seed proteome response of Fraxinus mandshurica Rupr. to dehydration (to a relative water content of 10%, which mimics seed dehydration) was investigated under four different conditions viz. 20 °C; 20 °C with silica gel; 1 °C; and 1 °C after pretreatment with Ca(2+). Proteins from seeds dehydrated under different conditions were extracted and separated by two-dimensional difference gel electrophoresis (2D-DIGE). A total of 2919 protein spots were detected, and high-resolution 2D-DIGE indicated there were 27 differentially expressed. Seven of these were identified using MALDI TOF/TOF mass spectrometry. Inferences from bioinformatics annotations of these proteins established the possible involvement of detoxifying enzymes, transport proteins, and nucleotide metabolism enzymes in response to dehydration. Of the seven differentially abundant proteins, the amounts of six were down-regulated and one was up-regulated. Also, a putative acyl-coenzyme A oxidase of the glyoxylate cycle increased in abundance. In particular, the presence of kinesin-1, a protein important for regulation and cargo interaction, was up-regulated in seeds exposed to low temperature dehydration. Kinesin-1 is present in all major lineages, but it is rarely detected in seed desiccation tolerance of woody species. These observations provide new insight into the proteome of seeds in deep dormancy under different desiccation conditions.